1995
DOI: 10.1073/pnas.92.21.9652
|View full text |Cite
|
Sign up to set email alerts
|

TRPC1, a human homolog of a Drosophila store-operated channel.

Abstract: In many vertebrate and invertebrate cells, inositol 1,4,5-trisphospate production induces a biphasic Ca2+ signal. Mobilization of Ca2+ from internal stores drives the initial burst. The second phase, referred to as storeoperated Ca2+ entry (formerly capacitative Ca2+ entry), occurs when depletion of intracellular Ca2+ pools activates a non-voltage-sensitive plasma membrane Ca2+ conductance. Despite the prevalence of store-operated Ca2+ entry, no vertebrate channel responsible for store-operated Ca2+ entry has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
396
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 561 publications
(408 citation statements)
references
References 41 publications
8
396
1
1
Order By: Relevance
“…Northern blot analysis has previously demonstrated highlevel expression of TRPC1 in heart, brain, testes and ovary, and lower levels of TRPC1 transcripts in all other human tissues tested with the exception of liver [10,11]. However, homologous TRPC1 mRNA in mouse liver could be detected by RT-PCR analysis, suggesting that low levels of TRPC1 transcripts may also be found in human liver.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Northern blot analysis has previously demonstrated highlevel expression of TRPC1 in heart, brain, testes and ovary, and lower levels of TRPC1 transcripts in all other human tissues tested with the exception of liver [10,11]. However, homologous TRPC1 mRNA in mouse liver could be detected by RT-PCR analysis, suggesting that low levels of TRPC1 transcripts may also be found in human liver.…”
Section: Discussionmentioning
confidence: 89%
“…It therefore appears that all three human TRPC genes may be ubiquitously transcribed. Wes et al [10] have reported that the TRPC2 cDNA sequence contains a stop codon in a position corresponding to residue 690 in TRPC1 (Fig. 2) and may therefore represent an expressed pseudogene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Transient receptor potential homologues have also been located in human sperm. 37,38 In addition, members of soluble Nethyl maleimide-sensitive factor attachment protein receptor proteins present in the acrosome region of mammalian sperm may also facilitate calcium entry, thereby leading to the AR. 39,40 The high intracellular free calcium concentration together with DAG leads to membrane fusion and finally acrosomal exocytosis.…”
Section: Signalling Events During Zp-mediated Acrosomal Exocytosismentioning
confidence: 99%